English Folk Ballads Collected By Cecil James Sharp in The Southern Appalachians: Genesis, Transformation and Ukrainian Parallels - Karbashevska, Oksana (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The purpose of this research, presented at the Conference sectional meeting, is to trace peculiarities of transformation of British folk medieval ballads, which were brought to the Southern Appalachians in the east of the USA by British immigrants at the end of the XVIIIth – beginning of the XIXth century and retained by their descendants, through analyzing certain texts on the levels of motifs, dramatis personae, composition, style and artistic means, as well as to outline relevant Ukrainian parallels. The analysis of such ballads, plot types and epic songs was carried out: 1) British № 10: “The Twa Sisters” (21 variants); American “The Two Sisters”(5 variants) and Ukrainian plot type I – C-5: “the elder sister drowns the younger one because of envy and jealousy” (8 variants); 2) British № 26: The Three Ravens” (2), “The Twa Corbies” (2); American “The Three Ravens” (1), “The Two Crows”(1) and Ukrainian epic songs with the motif of lonely death of a Cossack warrior on the steppe (4). In our study British traditional ballads are classified according to the grouping worked out by the American scholar Francis Child (305 numbers), Ukrainian folk ballads – the plot-thematic catalogue developed by the Ukrainian folklorist Оleksiy Dey (here 288 plots are divided into 3 spheres, cycles and plot types). The investigation and comparison of the above indicated texts witness such main tendencies: 1) the American counterparts, collected in the Appalachian Mountains, preserve the historic-national memory and cultural heritage of the British immigrant bearers on the level of leading motifs, dramatis personae, composition peculiarities, traditional medieval images, epithets, similes, commonplaces; 2) some motifs, characters, images, artistic means, archaic and dialectal English of the Child ballads are reduced or substituted in the Appalachian texts; 3) realism of American ballad transformations, which overshadows fantasy and aristocracy of their British prototypes, is similar to the manner of poetic presentation of the typologically-arisen and described events by the Ukrainian folk ballads and dumas .